2012
DOI: 10.3390/v4102182
|View full text |Cite
|
Sign up to set email alerts
|

Arenavirus Evasion of Host Anti-Viral Responses

Abstract: The innate response to infection by an Old World arenavirus is initiated and mediated by extracellular and intracellular receptors, and effector molecules. In response, the invading virus has evolved to inhibit these responses and create the best environment possible for replication and spread. Here, we will discuss both the host’s response to infection with data from human infection and lessons learned from animal models, as well as the multitude of ways the virus combats the resulting immune response. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Infection of rhesus macaques by the OW LCMV WE strain results in a fatal, Lassa fever-like disease, while the LCMV Arm strain does not induce disease. Interestingly, the LCMV WE strain also inhibited LCMV Arm-induced Toll-like receptor 2 (TLR2)/ Mal-dependent cytokine production in similar coinfection studies (47,48).…”
Section: Discussionmentioning
confidence: 76%
“…Infection of rhesus macaques by the OW LCMV WE strain results in a fatal, Lassa fever-like disease, while the LCMV Arm strain does not induce disease. Interestingly, the LCMV WE strain also inhibited LCMV Arm-induced Toll-like receptor 2 (TLR2)/ Mal-dependent cytokine production in similar coinfection studies (47,48).…”
Section: Discussionmentioning
confidence: 76%
“…P2 increases DNA binding of the activating RelA/p50 dimer of NF-κB, whereas P18 increases DNA binding of the repressive p50/p50 homodimeric form [136]. A similar mechanism was reported for suppression of IL-8 or IL-6 expression in cultured cells by virulent but not attenuated arenaviruses [137]. Meta-analyses of profiling studies in several laboratories identified transcription factors that were shared among some of the virulent infections.…”
Section: Profiling Disease Progressionmentioning
confidence: 90%
“…However, there was a minor disagreement in their results: for one group [189], DCs incubated with both infectious and inactivated LASV produced IL-1β, IL-8, little IL-10 and no TNF-α and for the other group [47], both DCs and MPs incubated with infectious LASV suppressed TNF-α, IL-1β and IL-10 while inactivated virus particles fostered production of those chemokines. The Lyon group concluded that the LASV stock of the Atlanta group ‘probably contained a significant quantity of noninfectious viral products [47],’ implying that replication of infectious particles is needed to suppress innate immunity, a finding later corroborated by others [137]. Two findings in human beings with LF lent weight to the idea that innate immunity is suppressed in severe infection: first, fatal cases of LHF had lower chemokine levels (IL-8 and IP-10) compared with survivors [166] and, second, IL-8 was the only cytokine that peaked in infected contacts of severe LASV cases who did not develop LF disease [71].…”
Section: Conclusion: the Importance Of Early Immune Responsementioning
confidence: 94%
See 1 more Smart Citation
“…Also, a calculated score was provided as a measure of the degree of binding interaction [57]. Toll-like receptor-2 (TLR2) can mediate high proinflammatory responses against LASV infection [58]. Therefore, TLR2 structure was used as the receptor (PDB ID: 3A7B) and the refined vaccine protein as the ligand [59].…”
Section: Molecular Docking Between the Vaccine And Tlr2 Receptormentioning
confidence: 99%